Pencemaran Logam Berat Hg, As, Cd Di Sedimen Sungai Langkowala Akibat Aktivitas Penambangan Kabupaten Bombana Sulawesi Tenggara - Nurbarasamuma Nurbarasamuma; Muhammad Chaerul (Jurnal Lingkungan Almuslim, 2022)
The purpose of this research is to analyze the level of heavy metal contamination and get pollution status on Langkowala river sediment in Watu-Watu village, Lantari Jaya sub-district, Bombana regency, Southeast Sulawesi province covering mercury (Hg), Arsenic (As) and Cadmium (Cd) mining activities. The method of sampling using grab sampling method and heavy metal analysis method was done in Laboratory using Atomic Absorbtion Spectrophotometry (AAS), then continued with data analysis using United State Enviromental Protection Agency (US EPA) standard quality standard. The test results of heavy metals samples including Mercury (Hg), Arsenic (As) and Cadmium (Cd) on Langkowala river sediments and paddy fields in Watu-Watu village on six sampling stations showed none of the parameters that exceeded the heavy metal standard on the sediment in accordance with the ratio of metal content to the standard of sediment quality standard according to United State Enviromental Protection Agency (US EPA).